How to open the treasure chest? optimising DNA extraction from herbarium specimens (2012)
Herbarium collections are potentially an enormous resource for DNA studies, but the use of herbarium specimens in molecular studies has thus far been slowed down by difficulty in obtaining amplifiable DNA. Here we compare a set of commercially available DNA extraction protocols and their performance in terms of DNA purity and yield, and PCR amplification success as measured by using three differentially sized markers, the rbcL barcoding marker (cpDNA), the LEAFY exon 3 (nrDNA), and the trnL(UAA) P6 loop (cpDNA). Results reveal large differences between extraction methods, where DNA purity rather than yield is shown to be strongly correlated with PCR success. Amplicon size shows similarly strong correlation with PCR success, with the shortest fragment showing the highest success rate (78%, P6 loop, 10–143 base pairs (bp)) and the largest fragment the lowest success (10%, rbcL, 670 bp). The effect of specimen preparation method on PCR success was also tested. Results show that drying method strongly affects PCR success, especially the availability of fragments longer than 250 bp, where longer fragments are more available for PCR amplification in air dried material compared to alcohol dried specimens. Results from our study indicate that projects relying on poor-quality starting material such as herbarium or scat samples should focus on extracting pure DNA and aim to amplify short target regions (<200–300 bp) in order to maximise outcomes. Development of shorter barcoding regions, or mini-barcodes within existing ones should be of high importance as only a few options are currently available; this is particularly important if we hope to incorporate the millions of herbarium samples available into barcoding initiatives and other molecular studies.